2005
DOI: 10.1111/j.1460-9568.2005.04411.x
|View full text |Cite
|
Sign up to set email alerts
|

Ventral pallidal neurons code incentive motivation: amplification by mesolimbic sensitization and amphetamine

Abstract: Neurons in ventral pallidum fire to reward and its predictive cues. We tested mesolimbic activation effects on neural reward coding. Rats learned that a Pavlovian conditioned stimulus (CS+1 tone) predicted a second conditioned stimulus (CS+2 feeder click) followed by an unconditioned stimulus (UCS sucrose reward). Some rats were sensitized to amphetamine after training. Electrophysiological activity of ventral pallidal neurons to stimuli was later recorded under the influence of vehicle or acute amphetamine in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
204
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 241 publications
(228 citation statements)
references
References 54 publications
22
204
1
Order By: Relevance
“…One line of evidence against a pleasure-causing role is that mesolimbic dopamine neurons may not reliably be activated by pleasure per se but instead by predictive, motivational, or attentional properties rather than hedonic properties of reward stimuli (Carelli 2004;Cheer et al 2007;Redgrave and Gurney 2006;Salamone et al 2007;Schultz et al 1997). Another line of evidence is that, when 'liking' versus 'wanting' are teased apart by brain manipulations, specific manipulation of dopamine signaling either up or down simply fail to shift 'liking' reactions to pleasure reliably in either animals or humans (Berridge 2007;Brauer and De Wit 1997;Cannon and Palmiter 2003;Evans et al 2006;Leyton 2008;Leyton et al 2002;Leyton et al 2005;Peciña et al 2003;Robinson et al 2005;Tindell et al 2005;Volkow et al 2002;Volkow et al 2006). A third line of evidence is that dopamine systems may also be activated by aversive or frankly non-rewarding stimuli, at least tonic dopamine release pulses that last on the order of a few minutes (Ferrari et al 2003;Horvitz 2000;Salamone 1994;Scott et al 2006).…”
Section: Controversial Subcortical Pleasure Generators? Dopamine and mentioning
confidence: 99%
See 2 more Smart Citations
“…One line of evidence against a pleasure-causing role is that mesolimbic dopamine neurons may not reliably be activated by pleasure per se but instead by predictive, motivational, or attentional properties rather than hedonic properties of reward stimuli (Carelli 2004;Cheer et al 2007;Redgrave and Gurney 2006;Salamone et al 2007;Schultz et al 1997). Another line of evidence is that, when 'liking' versus 'wanting' are teased apart by brain manipulations, specific manipulation of dopamine signaling either up or down simply fail to shift 'liking' reactions to pleasure reliably in either animals or humans (Berridge 2007;Brauer and De Wit 1997;Cannon and Palmiter 2003;Evans et al 2006;Leyton 2008;Leyton et al 2002;Leyton et al 2005;Peciña et al 2003;Robinson et al 2005;Tindell et al 2005;Volkow et al 2002;Volkow et al 2006). A third line of evidence is that dopamine systems may also be activated by aversive or frankly non-rewarding stimuli, at least tonic dopamine release pulses that last on the order of a few minutes (Ferrari et al 2003;Horvitz 2000;Salamone 1994;Scott et al 2006).…”
Section: Controversial Subcortical Pleasure Generators? Dopamine and mentioning
confidence: 99%
“…Regarding whether dopamine is needed at all to learn about rewards, several forms of reward learning have recently been shown to proceed normally in the brains of mice that completely lack dopamine signals (due to genetic manipulation that prevents dopamine synthesis by neurons), presumably both phasic and tonic signals (Hnasko et al 2005;Robinson et al 2005). Conversely, elevation of dopamine neurotransmission by a different genetic manipulation may fail to cause or alter teaching signals needed for new reward learning (Cagniard et al 2006a;Cagniard et al 2006b;Niv et al 2007;Tindell et al 2005;Yin et al 2006). Such observations raise room to doubts whether correlations between dopamine signals and learning necessarily imply that the dopamine has a strong causal role in learning.…”
Section: Dopamine-beyond Learning Too?mentioning
confidence: 99%
See 1 more Smart Citation
“…Yet, recent advances have shown that hedonic 'hotspots' are localized in the VP and rostromedial shell of the NAc, and that brains' ability to process pleasure implicate a complex interaction between DA operations and opioid systems (Peciña & Berridge 2005). So, DA's role in pleasure-processing is probably indirect and modulatory.…”
Section: Anhedonia (Hed)mentioning
confidence: 99%
“…Subsequently, IS has been invoked to explain results from electrophysiological and pharmacological experiments that manipulated DA activity in mesocorticolimbic areas of rats performing Pavlovian or instrumental conditioning tasks (Berridge & Robinson 1998;Berridge et al 2005;Robinson et al 2005). Further, increasing DA concentrations appears to change neural firing for signals that encode maximal incentive salience, but not maximal prediction (Tindell et al 2005).…”
Section: Incentive Salience (Is)mentioning
confidence: 99%